WOMENS RESISTANCE ON INSTAGRAM ACCOUNT @SINGLEMOMSINDONESIA - Tjajadi, Octavia Putri; Marta, Rustono Farady; Engliana, Engliana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Women are considered different from men. This has been a society stereotype from generation to generation. Feminists want to make changes, one of which is the resistance to the stigma of society that every human being has gender equality. One of the Instagram accounts that focuses on women's rights is @SingleMomsIndonesia, where every woman has the right to have their own life and needs to support each other. Their account shared a video, namely Para Puanâ€. This research uses a qualitative method and uses paradigm interpretive analysis semiotic and theory intertextual from Julia Kristeva. The result shows that every figure has different roles and human rights. Women's rights are also reflected in the rights of feminists who speak out for their rights. Most importantly, the woman must balance their roles in order, and egalitarian societal roles are necessary.